Оптимальные перелеты космических аппаратов с двухрежимными двигателями - Кифоренко, Б.Н.; Харитонов, А.М. (Прикладная механика, 2010)
An optimization problem of the interplanetary transfer of spacecraft with biregime nuclear rocket engine is formulated. The transfer trajectory is forming owing to combination
of parts of high and low engine thrust. An analysis of necessary conditions of optimality is
carried out. The solution of the problem on transfer Earth-Mars with duration of 180 astronomical days is given. Сформульовано проблему оптимізації міжпланетного перельоту космічного апарата з дворежимним ядерним ракетним двигуном. Траєкторія перельоту формується за рахунок комбінування ділянок великої та малої тяги. Проведено аналіз необхідних умов оптимальності. Наведено розв’язок задачі для перельоту Земля – Марс тривалістю 180 діб.